URANIUM(VI) SORPTION TO HEMATITE IN THE PRESENCE OF HUMIC ACID - IMPORTANCE OF CHARGE NEUTRALIZATION - Lenhart J.J.; Honeyman B.D. (My University, 1999)
A long-standing problem in aquatic geochemistry has been the incorporation of natural organic matter (NOM) into speciation models. The general effect of NOM on metal ion sorption by particles has been understood for some time, and significant progress has been made in elucidating some of the details of the role of NOM through the use of surrogate organic acids such as citric acid. However, a gap exists between the general observations that have been made of NOM behavior and the inclusion of NOM in surface chemical models for metal ion sorption. In this paper, we report on the results of a study on the sorption of U(VI) by hematite in the absence and presence of Suwannee river humic acid (HA) and over a range of other system conditions (e.g., pH, I). Essential HA characteristics (e.g., its acid/base, metal binding, and surface chemical properties) were ''captured'' by representing the HA as an assembly of monoprotic acids with assumed pK values and without explicit correction for electrostatic effects. The ternary system (hematite/HA/U(VI)) was simulated through the combination of the binary submodels (i.e., CO32-/hematite, U(VI)/HA, U(VI)/hematite, and HA/hematite) with model constants fixed at the values determined from simulations of the respective experimental systems. However, the ''summed-binary'' approach undersimulated experimental results, and the ternary system model required the postulation of two ternary surface (Type A) complexes composed of the uranyl ion, hematite surface sites, and the model ligands comprising the HA. Consideration of the HA in this manner permitted the simulation of HA effects on U(VI) sorption by hematite over a range of solution conditions using a general speciation model.